The Value Chain Mapping Of Porang Agribusiness In East Java Using AHP Approach - Utami, Ratih Apri; Aji, Joni Murti Mulyo; Ibanah, Indah (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Porang commodity produced in several district centers in East Java province, has good quality, so it is very good to be developed optimally. However, the supply chain performance that leads to the value chain still needs to be improved to be more efficient. Data analysis methods used in this study include value chain analysis and Analytical Hierarchy Process (AHP). The objectives of this research are: (1) to identify the mapping of the Porang value chain in East Java, and (2) to analyze the level of importance of the Porang value chain actors in East Java. Based on the results of the research, mapping the porang value chain in East Java stated that the actors consisted of porang spore suppliers and saprodi providers, producers were porang farmers, traders there were collectors, and porang processors acted as industrial consumers. There are three main streams in mapping the porang value chain, namely product flow, information flow and financial flow, starting from input suppliers, farmers, traders to processors/consumers. Based on the level of interest of the actors in the AHP hierarchical analysis, it can be seen the elements in decision making on the main activities, supporting activities and stakeholder performance. In the main activity, actors with superior importance were selected which showed that the implementation of product maintenance before resale has a very strong influence on value creators. In the supporting activities selected as the leading stakeholder, which shows that the implementation of general management of the company has a very strong influence on value creators. While the performance activity, which shows that the implementation of product maintenance before resale has an above average performance.